Profiling of hepatic metabolizing enzymes and nuclear receptors in rats with adjuvant arthritis by targeted proteomics. (29th July 2018) - Kawase, Atsushi; Tateishi, Shunsuke; Kazaoka, Akira
Abstract: Inflammatory conditions alter the expression and activity of factors influencing pharmacokinetics, such as metabolizing enzymes. The study examined alterations of hepatic protein levels of cytochrome P450 (CYP), UDP‐glucuronosyltransferase (UGT) and nuclear receptors in rats with adjuvant‐induced arthritis (AA rats), an inflammatory animal model, by liquid chromatography–tandem mass spectrometry‐based targeted proteomics. The protein levels of CYP1A1, CYP1A2, CYP2A1, CYP2A3, CYP2C6, CYP2C12, CYP2D3, CYP2E1, CYP3A9, UGT1A1 and UGT1A2/3 in liver microsomes of AA rats were significantly lower than those in control rats. The protein levels of constitutive androstane receptor (CAR) and retinoid X receptor α (RXRα) in the cytoplasm and nucleus were also significantly decreased, to approximately 60% of the control levels. The decreased protein levels of CYP1A2, CYP2C6, CYP2D3, CYP2E1 and UGT1A1 were potentially associated with downregulation of CAR or RXRα expression in the nucleus.